O1.2. DECREASED ACTIVATION IN TEMPOROPARIETAL JUNCTION IN INDIVIDUALS WITH PSYCHOSIS AND BIOLOGICAL FIRST-DEGREE RELATIVES DURING IMPLICIT THEORY OF MIND. (9th April 2019) - Kent, Jerillyn; Burton, Philip; Sponheim, Scott
Abstract: Background: Individuals with schizophrenia are known to have deficits in social cognition, including theory of mind. Impaired theory of mind has also been reported in first degree biological relatives of individuals with schizophrenia. However, there have been only a few investigations into the neural correlates of theory of mind dysfunction in relatives of individuals with schizophrenia. The current study examined neural activity in individuals with psychosis and first-degree biological relatives during implicit theory of mind, a more automatic and less cognitively demanding component of this social cognitive process. Methods: Fifty-eight individuals participated in this study; data were collected in the context of a Human Connectome Project study related to human disease focused on psychosis. Participants were 21 individuals with a psychotic disorder, 14 biological first-degree relatives, and 23 controls. Participants underwent fMRI while completing an implicit theory of mind task. In this task, 20 second animations were shown depicting two triangles, with the movement of the triangles corresponding to one of three conditions. In the Theory of Mind condition, the triangles appeared to be interacting with each other and taking each other's thoughts and feelings into account. In the Physical Interaction condition, the movement of the triangles appeared related (i.e., mirror movement), but the shapes did not appear to be having a social interaction/taking each other's thoughts and feelings into account. In the Random condition, the shapes' movements were unrelated to each other. There were six animations presented for each condition across 3 runs, and after viewing each video clip participants selected which type of interaction they believed was going on. fMRI data were analyzed using a canonical preprocessing pipeline in FSL, and first-level GLM analyses modeled neural activity that corresponded to viewing the different types of animations. Results: For the Theory of Mind minus Physical Interaction contrast, there was significantly greater activation in controls compared to both individuals with psychosis and relatives. Specifically, there was one significant cluster of greater activation in controls versus individuals with psychosis (k = 388), and one significant cluster of greater activation in controls versus relatives (k = 287) (corrected cluster significance threshold of p = 0.05). Both of these clusters included right temporoparietal junction (TPJ). There were no areas of activation that were significantly greater in either individuals with psychosis or relatives compared to controls, and there were no significant differences in activation between individuals with psychosis and relatives. Discussion: Results revealed decreased TPJ activation in both individuals with psychosis and relatives compared to controls. TPJ is involved in theory of mind, and abnormalities in TPJ activity have been reported in individuals with schizophrenia during theory of mind. Therefore, these results are consistent with previous literature, and the use of an implicit theory of mind task reduces the concern of confounds related to cognitive deficits. Findings of decreased TPJ activation during implicit theory of mind in relatives suggests that abnormal neural activity during theory of mind may be associated with unexpressed genetic liability for psychosis.